Enhanced degradation of 2,4-dichlorphenoxyacetic acid herbicide by CaO2 activated by Fe(II) and ultrasound irradiation: Practical insight and mineralization - Eslami, Akbar; Mahdipour, Fayyaz; Maleksari, Hajar Sharifi; Varank, Gamze; Ghasemi, Seyed Mehdi; Nejatian, Parisa; Bagheri, Amin; Madihi-Bidgoli, Soheila (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2023)
CaO2 was activated by Fe(II) and ultrasound (US) irradiation to degrade 2,4-dichlorphenoxyacetic acid (2,4-D) for the first time. Among transition metals (Fe, Cu, Mn and Co), Fe(II) had the best performance for the activation of CaO2. The impact of pH, CaO2 and Fe(II) concentration was studied, and under optimal situation similar to 91% of 2,4-D was degraded during 60 min reaction time. The quenching experiments showed that the hydroxyl radical was the main factor for the destruction of 2,4-D while superoxide anions had a minor role. The bicarbonate ions and acid humic exhibited a strong inhibitory effect on the performance of CaO2/US/Fe(II) process. Carbon and chlorine mineralization of 2,4-D degradation was investigated; around 41% of C and 35% of Cl were mineralized during 60 min reaction time. The function of CaO2/US/Fe(II) process was studied on real drainage and other organic pollutants, and the results showed that the CaO2/US/Fe(II) process can be practical for water treatment. Finally, intermediates of 2,4-D degradation were identified, a pathway was proposed, and the toxicity of intermediates was assessed by ECOSAR software.
Keywords: Herbicide; Fenton Oxidation; Mineralization; Calcium Peroxide; Toxicity Evaluation; FENTON-LIKE PROCESS; OXIDATION PROCESSES; VALENT IRON; WASTE-WATER; REMOVAL; PERFORMANCE; PEROXIDE; 2,4-D; H2O2; PEROXYMONOSULFATE; Chemistry; Engineering